The Design of Rice Milling and Screening Systems Uses the DC Motor PID Method - Cahya, Aulia Adi; Puriyanto, Riky Dwi (Control Systems and Optimization Letters, 2023)
Rice is one of the staple foods of most Indonesian people, the processing of rice derived from rice plants goes through many stages, one of which is rice milling and sifting. This research aims to make it easier for farmers to do milling and screening, the system will utilize DC motor rotation which is suitable for application in milling and screening, this system also utilizes electrical energy obtained from sunlight so it is more efficient and environmentally friendly. The milling DC motor will use the PID method with a value of P=25, I=50 and D=5 with a setpoint of 250, while the winnowing motor will use a PWM setting of 200 with a voltage of 7.07 V and a motor RPM of 348. This study also has digital scales. which can easily find out the results in units of grams with a maximum capacity of 5,000 grams. The prototype of this rice grinder and sifter has a success rate of testing sensors and motors in the range of 50%, even though the milling results can be said to be less than optimal, the screening results can work according to function, as well as solar panels that can optimally provide power to move the actuators and sensors. sensors in this system.